The Psychological Impact of Participation in Victim-Offender Mediation on Offenders: Evidence for Increased Compunction and Victim Empathy - Jonas, Jiska; Zebel, Sven; Claessen, Jacques; Nelen, Hans (Frontiers in Psychology, 2022)
An extensive body of literature claims that participation in victim-offender mediation (VOM) can decline the risk of reoffending. However, relatively little is known about which intermediate psychological changes the VOM-process elicits that may underly this effect. It was hypothesized that offenders who have participated in mediation feel more responsible, guilty, and ashamed about the (damage of the) offense, show more empathy towards the victim, experience their offense more as a moral failure, show a greater intention to desist, and view their relation with the victim, relatives, and the community as more positive after VOM compared to offenders who do not participate in VOM. In addition, it was also hypothesized that offenders who have participated in VOM have lower feelings of rejection, are less concerned for condemnation, experience a lower threat to their social moral identity, and show less victim blame. To this end, offenders who participated in a VOM program in the Netherlands were compared to offenders who were willing, but did not participate (total N = 86). A quasi-experimental, pre- and postmeasure research design was used to compare these groups. Our findings tentatively suggest a victim empathy and compunction focused psychological change: offenders who participated in VOM reported significantly more responsibility-taking and victim empathy afterwards, felt more guilt and shame, and experienced higher moral failure. Offenders also reported feeling significantly less awkward to meet the victim again after VOM, compared to those who were willing, but did not participate. Future research should address how and to what degree these psychological changes translate into a lower risk of reoffending.